Biological Chemical Laboratory at Dow Chemical Company - Dow Chemical Company (1955)
General view of an unidentified employee weighing a rabbit in the Dow Chemical Company's Biological Chemical Laboratory. Several rows of pens containing other rabbits are visible in the background. The laboratory commonly conducted research and testing related to the development of a range of biologically active products for use in the pharmaceutical, biological, animal healthcare, and agricultural industries.
Keywords: Employees; Laboratories; Dow Chemical Company; Biochemistry; Laboratory animals